Desenvolvimento de um sistema de ventilação forçada para secar o fio máquina na laminação a frio de vergalhões - Rocha, Fábio Augusto Costa da (2012)
The national steel industry has been modernized. Indeed, its processes seek stability in the production area. The cold rolling of rebars is a process which is evolving: technological advance allows such machines, for example, reach speeds up to 17 m/s. However, high speeds bring the probability of interruptions in production. At Gerdau, the cold rolling mills are common, and one of the main reasons identified by stopping production units throughout Brazil is just a interruption in machinery because of wire rod wet by the rain water. This fact is because the lubricant and has very small particles with the passage of the wire rod wet, expands, and deposited on the cassettes - the equipment responsible for a reduction of the wire rod - locking the bearings of the rolls. The solution adopted for the removal of water from the wire rod was the installation of a system compound of a tube with bearings at the ends two nozzles spaced 120° from e ach other. In theses nozzles are hoses coupled, in turn, are connected to a centrifugal fan. The implementation of this system guaranteed, thus, the stability of the process, even on rainy days.